2010
DOI: 10.3109/03009742.2010.523012
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with low-dose prednisolone is associated with altered body composition but no difference in bone mineral density in rheumatoid arthritis patients: a controlled cross-sectional study

Abstract: RA patients treated with low-dose prednisolone had significantly higher FM than patients without prednisolone, an effect that was independent of current inflammation. However, there was no association between prednisolone treatment and muscle mass or BMD. Thus, the net effect of prednisolone on body composition and bone is different in inflammatory diseases such as RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 39 publications
1
22
1
3
Order By: Relevance
“…In addition, the effects of steroid usage on bone loss in RA may be more pronounced in the early phase of disease and therapy; however, mean disease duration in our study group was approximately 10 years (41). In a recent study, it was also shown that RA patients treated with low-dose prednisolone had a similar BMD compared with patients who had not been treated with prednisolone (45). In this study, the authors hypothesized that the suppressive effect on bone synthesis of low-dose glucocorticoids may be compensated for by its ability to hamper the inflammatory-mediated increase in bone resorption; therefore, the net effect of prednisolone on body composition and bone may be different in inflammatory diseases, such as RA.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, the effects of steroid usage on bone loss in RA may be more pronounced in the early phase of disease and therapy; however, mean disease duration in our study group was approximately 10 years (41). In a recent study, it was also shown that RA patients treated with low-dose prednisolone had a similar BMD compared with patients who had not been treated with prednisolone (45). In this study, the authors hypothesized that the suppressive effect on bone synthesis of low-dose glucocorticoids may be compensated for by its ability to hamper the inflammatory-mediated increase in bone resorption; therefore, the net effect of prednisolone on body composition and bone may be different in inflammatory diseases, such as RA.…”
Section: Discussionmentioning
confidence: 67%
“…Westhovens et al [35], AkAr et al [36] and engvAll et al [37] found no influence of glucocorticoid treatment on total "bone mineral density". The authors concluded that it may be due to small sample size.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are empowered by a recent study also investigating the influence of a low-dose prednisone therapy (5-7.5 mg) versus placebo over 2 years on BMD and body fat. The trial consisted of 50 patients in each arm and brought up no association between prednisone therapy and BMD, though the body fat mass in the prednisone group increased significantly [70].…”
Section: Osteoporosismentioning
confidence: 99%
“…This recommendation probably derives from the observations of RA itself interfering with bone metabolism [69,73] and the growing evidence of prednisone counteracting that negative inflaming impact, especially in early RA and low-dose use [68,70].…”
Section: Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation